Saccular function is associated with both angular and distance errors on the triangle completion test. Issue 11 (November 2019) - Anson, E.R.; Ehrenburg, M.R.; Wei, E.X.; Bakar, D.; Simonsick, E.; Agrawal, Y.
Highlights: Gravitational cues detected by the saccule contribute to estimation of place and heading direction. Spatial orientation errors increase with both aging and reduced saccular function. Vestibular function was not associated with distance walked. Abstract: Objective: The present study was designed to determine whether healthy older adults with age-related vestibular loss have deficits in spatial navigation. Methods: 154 adults participating in the Baltimore Longitudinal Study of Aging were tested for semicircular canal, saccular, and utricular function and spatial navigation ability using the blindfolded Triangle Completion Test (TCT). Multiple linear regression was used to investigate the relationships between each measure of vestibular function and performance on the TCT (angular error, end point error, and distance walked) while controlling for age and sex. Results: Individuals with abnormal saccular function made larger angular errors (β = 4.2°, p < 0.05) and larger end point errors (β = 13.6 cm, p < 0.05). Independent of vestibular function, older age was associated with larger angular (β's = 2.2–2.8°, p's < 0.005) and end point errors (β's = 7.5–9.0 cm, p's < 0.005) for each decade increment in age. Conclusions: Saccular function appears to play a prominent role in accurate spatial navigation during a blindfolded navigation task. Significance: We hypothesize that gravitational cues detected by the saccule may be integrated into estimation of place as well as heading direction.